The Potential Role for Myoinositol in the Prevention of Gestational Diabetes Mellitus - Werner, Erika F.; Froehlich, Rosemary J. (American Journal of Perinatology, 2016)
More than 9% of overweight and obese women develop gestational diabetes mellitus (GDM) during pregnancy. Myoinositol is a promising supplement that may represent the first GDM-risk modifier that could be implemented on a population-level. It has been shown in animal and small human trials to prevent GDM through its insulin-mimetic properties. In animal studies, it also appears to decrease intra-abdominal adiposity and protect against diabetic embryopathies. In humans, four small randomized trials have demonstrated that myoinositol supplementation can lead to more than a 50% rate reduction in GDM compared with placebo. We now need a large, multicentered randomized controlled trial to demonstrate whether myoinositol has not only the promised impact on GDM rates, but also an effect on important secondary outcomes intricately linked to GDM, such as birth weight and neonatal intensive care unit admission.
Keywords: gestational diabetes mellitus; diabetes mellitus; obesity; polycystic ovarian syndrome; myoinositol; inositol; disease prevention